PLACENTAL MORPHOHISTOMETRIC ALTERATIONS IN PREGNANCIES COMPLICATED BY MATERNAL CARDIAC DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study examines morphogistometric alterations in placental structures among pregnant women with congenital and acquired heart defects. Comparative analysis of 87 placentas revealed significant deviations in villous architecture, vascular density, and intervillous space morphometry. Results demonstrate decreased terminal villous diameter (42.3±3.7 μm vs 68.5±4.2 μm), increased syncytial knot frequency (18.7±2.1 per field vs 6.3±1.4), and reduced capillary density (31.2±4.8% vs 47.6±3.9%) compared to controls, indicating compensatory-adaptive mechanisms in response to maternal hemodynamic compromise.